The Effect of Self Compassion on Forgiveness in Wives Who Experience Domestic Violence - Zahlevi, Fadhla Khairatu; Rusli, Devi (In Trend : International Journal of Trends in Global Psychological Science and Education, 2024)
Domestic violence is rampant among married couples. Various types of domestic violence can have psychological impacts such as anxiety, fear, and depression. Forgiveness is one of the methods for victims of violence to prevent psychological disorders. Self-compassion provides kindness and helps with emotion regulation so that it helps the forgiveness process. The method used is quantitative with regression analysis to determine the effect of self-compassion on forgiveness in wives who experience domestic violence. The sample of this study was wives who were victims of domestic violence as many as 90 women. Forgiveness is measured by The Transgression-Related Interpersonal Motivation Inventory (TRIM-18) scale (McCullough, 2003) and self-compassion is measured by The Self Compassion Scale (SCS) scale (Neff, 2003). Both scales have gone through validity and reliability tests. The results showed that there was no effect of self-compassion on forgiveness in wives who experienced domestic violence.